Model reduction for friction-induced vibration of multi-degree-of-freedom systems and experimental validation. (September 2018) - Li, Zilin; Wang, Xiaocui; Zhang, Qi; Guan, Zhenqun; Mo, Jiliang; Ouyang, Huajiang
Highlights: A model reduction method for friction induced-vibration of real friction systems is put forward. It is based on mode synthesis and accommodate friction contact interfaces. It is theoretically validated on a 9-degree-of-freedom friction system. It is experimentally validated on a customised tribometer. Numerical simulation and experimental test indicate this is an accurate and efficient method for stability analysis of real friction systems. Abstract: Most frictional systems are composed of components that are in sliding contact. Thus they have natural contact interfaces on which normal contact forces and tangential friction forces are acting. These real systems are complicated and friction brings further complexity, which presents a challenge to their dynamic analysis and control. In this paper, a model reduction strategy for complicated frictional systems is put forward based on the idea of mode synthesis, and its applications and experimental validation are presented. Firstly, the accuracy of the reduction method and the feasibility of the reduced model in stability analysis are verified on a theoretical multi-degree-of-freedom frictional system. Then, a tribometer in the form of a pad-on-disc test rig is designed and built and its corresponding detailed finite element (FE) model is constructed. A specific reduction strategy for this real friction system which involves direct contact at the pad-disc interface, is proposed. It is found that the reduced model with 80 modes of each of the two substructures of the system can already correctly predict the mode-coupling instability of the full FE model (which has over 900, 000 degrees of freedom) of the real system, and unstable frequencies that are fairly close to the unstable frequencies of the FE full model computed by Abaqus CEA and the vibration frequencies measured in the test on the tribometer, which demonstrates the efficiency and accuracy of the model reduction strategy for dynamic analysis of real friction systems. Its computational efficiency would be even much greater when applied to nonlinear dynamic analysis of real friction systems. Model reduction for friction-induced vibration validated by experiments has not been reported in the literature. Graphical abstract: Image, graphical abstract